(untitled) (Journal of the College of Basic Education, 2022)
Alongside the progress of scientific and technical knowledge, there emerge new concepts, terms, titles and views that contribute to the construction, remediation, and development of the intellectual, cultural and human system starting in the first place from remedies stemmed within the scientific aspect in order to begin the process of building humankind and its reality in which he/she lives. Between unfamiliarity and peculiarity the logic of primitive culture manifests itself as an individual entity that has its characteristics stemming from its various components that have posed rich, inspiring, intact source of structural modernism which imprinted with its shape and quality a documentary film that has, following a baby-step scientific journey, become a discipline adopted by the world’s greatest universities, and its primary premises focus on Anthropology and Ethnography; embraced, safeguarded and integrated by the visual cinematic language elements. This discipline and film type that was anchored upon, undertook to bear the burden of concerns and sufferance off the human societies that are strange to us and to our world, and are featured with its own world that preferred self-seclusion blanketing itself with leaves of trees in the forests with their yet-to-be explored nature at times, and the forefathers’ heritage at other times, or scattered in the holes of desert to stay away from anything that may contaminate its purity and decipher its secrets of language, habits, traditions, ceremonies, rituals and social structure, and even their tribal disputes.